The Effects of Kinematic Magnetohydrodynamics on the Atmospheric Circulation of Eccentric Hot Jupiters - Hayley Beltz; Willow Houck; L. C. Mayorga; Thaddeus D. Komacek; Joseph R. Livesey; Juliette Becker (The Astrophysical Journal)
Hot Jupiters are typically considered to be tidally locked due to their short orbital periods. The extreme irradiation can result in atmospheric species becoming thermally ionized on the dayside, which then interact with the planet’s magnetic field by resisting flow across magnetic field lines, shaping the atmospheric structure. However, an eccentric orbit results in temporally dependent irradiation and a nonpermanent dayside, as the planet–star distance can change drastically during its orbit. In this paper, we present 3D atmospheric models of TOI-150b, an eccentric ( e = 0.26), Jupiter-mass (∼1.75 M _Jup ) planet whose equilibrium temperature varies from 1300 to 1700 K. We conduct simulations for magnetic field strengths ranging from 0 to 30 Gauss using the kinematic magnetohydrodynamics (MHD) approach. When compared with simulations of the planet assuming a circular orbit, we find that the eccentric orbit results in a strengthened and narrowed equatorial jet, westward winds at midlatitudes, and a phase-dependent thermal inversion. The strength and magnitude of these effects scale with the chosen global magnetic field strength. We also generate high-resolution ( R = 100,000) emission spectra to study net Doppler shifts and find interorbit spectroscopic variability at moderate magnetic field strengths, as well as decreased Doppler broadening as magnetic field strengths increase. This work represents the first time that the kinematic MHD approach has been applied to an eccentric hot Jupiter and highlights the importance of a locally calculated, temperature-dependent magnetic drag prescription for predicting atmospheric structure and resulting spectra.